PENINGKATAN KUALITAS KARKAS AYAM KAMPUNG SUPER MELALUI PERBAIKAN SISTEM PEMOTONGAN DI DESA ALEBO, KECAMATAN KONDA, KABUPATEN KONAWE SELATAN - Widhi Kurniawan; Ali Bain; Syamsuddin Syamsuddin; Purnaning Dhian Isnaeni; Wa Laili Salido; Asma Bio Kimestri; Hamdan Has; Putu Nara Kusuma Prasanjaya (Universitas Nusa Cendana, 2021)
Chicken slaughter had to fulfill requirements such as the slaughter done in Islamic ways and the meat processed hygienically in order to produce safe, healthy, whole, and halal. Partner farmer at Alebo, Konda Sub-district, Konawe Selatan Regency implemented a simple slaughter system with less hygienic tools and procedures that increased the risk of contamination in meat. This community partnership program aimed to increase the farmer’s information and skill in managing native chicken slaughterhouses in order to produce better carcass and fish feed from slaughter waste. The methods used in this program were physical and non-physical methods which consisted of the slaughterhouse renovation, chicken slaughter, and carcass packaging training, fish feed production using slaughter waste training, discussion, and public lecture. Results of the program show that partner farmers are able to implement Islamic and hygienic slaughter processes and use better packages for the carcass. The farmers also understand the importance of slaughter waste processing and producing fish feed as an additional product of the slaughterhouse.